2018
DOI: 10.3390/nu10030270
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Single Dose of a Polyphenol-Rich Seaweed Extract on Postprandial Glycaemic Control in Healthy Adults: A Randomised Cross-Over Trial

Abstract: This study investigated the impact of a polyphenol-rich seaweed extract on postprandial glycaemia in healthy adults, and, as a secondary outcome, the influence of ethnicity on these outcomes. Thirty-eight volunteers (26 non-Asian, 12 Asian) aged 19 to 56 years participated in this double-blind, placebo-controlled, randomised cross-over trial. Participants each consumed a low (500 mg), and high (2000 mg) dose of the polyphenol-rich brown seaweed (Fucus vesiculosus) extract, as well as a cellulose placebo (2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 48 publications
3
68
1
Order By: Relevance
“…Journal of Diabetes Research revealed that the ability of a commercial mixture of Ascophyllum nodosum and Fucus vesiculosus to inhibit alpha-amylase and alpha-glucosidase activity after 3 hours of ingestion. Moreover, the consumption of 500 mg and 2000 mg of brown seaweed Fucus vesiculosus did not affect the postprandial blood glucose and postprandial insulin levels in healthy volunteers [61]. Further clinical studies revealed the physiological effect of seaweed supplementation of the species from genus Laminaria decreased the fasting blood glucose and two hours postprandial blood glucose levels in patients with type 2 diabetes (control: 254:4 ± 22:8 mg/dl and seaweed supplementation: 203:1 ± 12:3 mg/dl) without affecting the glycated haemoglobin level [62].…”
mentioning
confidence: 82%
“…Journal of Diabetes Research revealed that the ability of a commercial mixture of Ascophyllum nodosum and Fucus vesiculosus to inhibit alpha-amylase and alpha-glucosidase activity after 3 hours of ingestion. Moreover, the consumption of 500 mg and 2000 mg of brown seaweed Fucus vesiculosus did not affect the postprandial blood glucose and postprandial insulin levels in healthy volunteers [61]. Further clinical studies revealed the physiological effect of seaweed supplementation of the species from genus Laminaria decreased the fasting blood glucose and two hours postprandial blood glucose levels in patients with type 2 diabetes (control: 254:4 ± 22:8 mg/dl and seaweed supplementation: 203:1 ± 12:3 mg/dl) without affecting the glycated haemoglobin level [62].…”
mentioning
confidence: 82%
“…The mechanisms of anti-diabetic action by seaweed have been attributed to compounds including phlorotannins, fucoxanthin, polyphenolics, and polysaccharides (Kellogg et al 2014;Murray et al 2018) which inhibit hepatic gluconeogenesis, and reduce the activity of digestive enzymes such as α-amylase, α-glucosidase, lipase, and aldose reductase (Sharifuddin et al 2015). Seaweeds and their extracts may alleviate the health epidemic of type 2 diabetes which can lead to nephropathy, blindness, peripheral neuropathy with loss of limb extremities, and premature death (Yamazaki et al 2018).…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…A recent study conducted by Murray et al [164] found that a single dose up to 2000 mg of a polyphenol-rich Fucus vesiculosus Linnaeus extract had no additional lowering effect compared to placebo on postprandial blood glucose or plasma insulin in healthy adults. The authors suggested that future studies with polyphenol-rich marine algal extracts should aim to investigate the glycemic modulating effects in at-risk populations, such as pre-diabetics, since the results may be different.…”
Section: Clinical Trialsmentioning
confidence: 99%